Overcoming T-cell exhaustion in glioblastoma: A narrative review - Xuya Wang; Xisen Wang; Jiabo Li (Glioma, 2022)
Immunotherapy is typically ineffective against glioblastoma (GBM) due to inherent and adaptive resistance. Initial immunotherapy results for GBM have been disappointing. In this regard, T-cell exhaustion is a major barrier to successful treatment. The recognition of exhausted CD8+ T cell (Tex) pedigree is currently undergoing a paradigm shift. This review introduces major findings in this field to provide an up-to-date perspective on epigenetic, transcriptional, metabolic, and spatial heterogeneity, as well as interactions with tumor microenvironment cells of anti-tumoral CD8+ Tex from the following aspects: (i) Epigenetic and transcriptional mechanisms underlying T-cell exhaustion, (ii) Metabolic factors underpinning T-cell exhaustion, (iii) Contribution of multiple cell types to T-cell exhaustion, (iv) Occurrence of T-cell exhaustion at multiple locations, and (v) T-cell exhaustion may not always be terminal. These novel insights afford a wide range of new therapeutic approaches to overcome T-cell exhaustion in GBM.